ECRANISATION OF THE SERENDIPITY NOVEL BY ERISCA FEBRIANI INTO THE SERENDIPITY MOVIE BY DIRECTOR INDRA GUNAWAN - Saraswati, Listya Ayu; Kamiliya, Sekar Aneira (CrossOver Journal of Adaptation Studies, 2023)
The purpose of this study is to look into the ecranisation or adaptation of literary works of plot, characters, and settings in the form of shrinking, adding, and changing variations in Erisca Febriani’s novel Serendipity to Indra Gunawan’s film of the same title, as well as the reasons for the ecranisation. The novel and the film are both used as primary data sources. The primary data for this study are narration and dialogues from the novel, as well as scenes and script conversations from the film. Secondary data includes popular articles, interviews, and other online social media records from the author and filmmaker. To collect data, descriptive qualitative method is used. This research uses adaptation theory from Hutcheon (2013) to analyze the data, particularly the ’what’ and ’why’ frameworks. As a result, shrinking, adding, and changing variations in plot, characters, and setting exist in the process of ecranisation from Serendipity novel to film. The only reason the author and film maker made this adaptation was economic reasons to make more money and target a larger audience.